The Effect of Yiqi Huoxue Tongluo Decoction on Spinal Cord Microglia Activation and ASK1-MKK3-p38 Signal Pathway in Rats with Diabetic Neuropathic Pain. (19th May 2022) - Wang, Fanjing; Tang, Heyong; Ma, Junlong; Cheng, Lianzhi; Lin, Yixuan; Zhao, Jindong; Shen, Guoming; Fang, Zhaohui; Jiang, Aijuan
Abstract : Diabetic neuropathic pain (DNP) is one of the most common chronic peripheral neuropathies in diabetes mellitus (DM). Objective . To observe the underlying mechanism of the effects of Yiqi Huoxue Tongluo Decoction (YQHX) on DNP rats. Methods . SD rats were intraperitoneally injected with 35 mg/kg streptozotocin (STZ) to prepare DNP models and were treated with YQHX for 8 weeks. Results . Studies have shown that the drug restores some levels of MWT, TWL, and MNCV, downregulates the levels of inflammatory factors IL-6, IL-1 β, and TNF- α, downregulates the levels of ASK1-MKK3-p38, and weakens the level of OX42 activation. Conclusion . Yiqi Huoxue Tongluo Decoction can relieve DNP by affecting the activity of spinal cord microglia and the ASK1-MKK3-p38 signaling pathway, thereby reducing the central sensitization caused by the inflammatory response of DNP rats.